2018
DOI: 10.3390/molecules23092346
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Tea Catechins and Its Improvement

Abstract: Many in vitro studies have shown that tea catechins had vevarious health beneficial effects. However, inconsistent results between in vitro and in vivo studies or between laboratory tests and epidemical studies are observed. Low bioavailability of tea catechins was an important factor leading to these inconsistencies. Research advances in bioavailability studies involving absorption and metabolic biotransformation of tea catechins were reviewed in the present paper. Related techniques for improving their bioav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
169
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(174 citation statements)
references
References 110 publications
1
169
0
4
Order By: Relevance
“…The anti-inflammatory and antioxidative properties of flavan-3-ol compounds [32], combined with significant cholinesterase inhibitory activity demonstrated by EGCG in this study, results in an attractive group of compounds which could be recommended for the treatment of AD symptoms. Further investigation of EGCG and other related flavan-3-ols in vivo is suggested to gain a fuller understanding of the properties of these compounds.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The anti-inflammatory and antioxidative properties of flavan-3-ol compounds [32], combined with significant cholinesterase inhibitory activity demonstrated by EGCG in this study, results in an attractive group of compounds which could be recommended for the treatment of AD symptoms. Further investigation of EGCG and other related flavan-3-ols in vivo is suggested to gain a fuller understanding of the properties of these compounds.…”
Section: Discussionmentioning
confidence: 72%
“…Studies have shown that concentrations of flavan-3-ols between 1-100 µmol/L in human cells are sufficient to produce benefits such as antioxidation and anti-inflammation [32]. However, oral administration, the consequent metabolism and limited passive absorption from the gastrointestinal tract, results in flavan-3-ol compounds being able to produce only very low plasma concentrations, typically below the micromolar range [32].…”
Section: Bioavailability and Cellular Accumulation Of Flavan-3-olsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanostructure-based drug delivery systems has become popular for upgrading drug bioavailability. It has been reported that nanocarriers with sustained release of EGCG loading have apparent bioavailability even at slight doses, that traditional formulations is far beyond reach (Cai et al, 2018). Encapsulation materials including lipids (Dag & Oztop, 2017), proteins (Li, Lim, & Kakuda, 2009), carbohydrate (Admire, Nicolazzo, & Ian, 2011) can be used as a carrier to improve the solubility, prevent intestinal degradation, increase penetration from the small intestine, and the concentration in the blood, thereby improving the bioavailability of catechins including EGCG (Hu, Liu, Zhang, & Zeng, 2017;Ye, Liu, Shang, Chen, & Wang, 2018).…”
Section: Tp Regulate the Bioavailability Of Intestinal Microorganismsmentioning
confidence: 99%
“…Catechins are volatile and can be easily degraded and metabolized by interactions with hydroxyl groups on phenol rings under physiological conditions. Even when administered intravenously, catechins are partly degraded before they reach the target tissues (25). Catechins also undergo metabolic breakdown in the liver, small intestine, and colon (26).…”
Section: Catechinsmentioning
confidence: 99%